The Marketing System Impact On Consumer’s Psychological Dimensions :‘’ Motives and Perception’’; an Analytical presentation within an Ethical Perspective. - Bensalah , Abderrezak (Journal of Excellence for Economics and Management Research, 2017)
We aim through this study to show how the marketing system works on finding the different psychological effects that have effect on both psychological dimensions ‘’motives and perception’’ that influence the consumer for generating the purchasing behavior within the competitive environment. The analytical method has been adopted to conduct this study in order to ethically discuss the different uses of the psychological dimensions “perceptions and motives” Findings have revealed that marketing aims to deal with perception and motives considered as strong components in shaping the purchasing behavior. The marketing system effect occurs not only within the purchasing process limits, but it steps into a type of a social exchange, this because of the huge number of marketing messages that have impact on consumers, and both critical psychological dimensions ‘’perception and motives’’ regarding their sensibility towards those effects. Another result suggests that marketing strongly influences the consumer regarding its powerful effect in terms of directing the behavior. Therefore, those marketing messages must be discussed within a scientific and ethical framework so that a general framework will be made for regulating the marketing system outputs in order to make them as factors of an economic and social development and for a consumer protection